Pengaruh Reputasi Terhadap Minat Beli Produk Skincare di Shopee - Cindy Ayu Agustin; Gracia Reveria Hellianto (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
Technological developments have caused changes in consumer shopping behavior from offline to online which has led to the emergence of various types of online marketplace platforms. In this study, we will discuss the impact of seller's reputation, quality of seller services, and customer trust on interest in buying cosmetic products at Shopee. This research is an associative quantitative research with survey method through questionnaires as the main instrument. The results showed that there was a relationship and significant influence between reputation, quality of service sellers, and customer trust on buying intention on skincare product at Shopee.